2012
DOI: 10.1007/s00737-012-0317-8
|View full text |Cite|
|
Sign up to set email alerts
|

Less depressed or less forthcoming? Self-report of depression symptoms in women preparing for in vitro fertilization

Abstract: PURPOSE While depression has been associated with infertility treatments, it is not routinely assessed in women prior to undergoing in vitro fertilization (IVF) treatment. Findings are mixed regarding the degree to which women report depression prior to IVF. The purpose of this study was to: 1) examine response profiles in women preparing for IVF, and 2) compare responses to those of postpartum, primary care, and general population groups. METHODS Female IVF patients (n=321; 19 – 45 years) completed the PHQ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…However, one of the seven studies found no significant difference in depression scores between infertile and normal women (subscale of PGWB, m = 15.4 vs. 15.3) [6], with the measurement point at 2-4 weeks before treatment. Contradictory findings were presented in a study conducted in the USA, indicating that incidences of major depressive disorders (MDD) and other depressive disorders (ODD) among IVF women were lower than among the primary care population (PHQ-9, MDD, 1 % vs. 10 %; ODD, 2 % vs. 6 %) [21], where the PHQ instruments were first developed and published [25]. A possible explanation for this finding proposed by the author was that the PHQ might not be an appropriate/ sensitive measure of distress for women at the pre-IVF treatment period [21].…”
Section: Depressionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, one of the seven studies found no significant difference in depression scores between infertile and normal women (subscale of PGWB, m = 15.4 vs. 15.3) [6], with the measurement point at 2-4 weeks before treatment. Contradictory findings were presented in a study conducted in the USA, indicating that incidences of major depressive disorders (MDD) and other depressive disorders (ODD) among IVF women were lower than among the primary care population (PHQ-9, MDD, 1 % vs. 10 %; ODD, 2 % vs. 6 %) [21], where the PHQ instruments were first developed and published [25]. A possible explanation for this finding proposed by the author was that the PHQ might not be an appropriate/ sensitive measure of distress for women at the pre-IVF treatment period [21].…”
Section: Depressionmentioning
confidence: 88%
“…The depression levels of women and/or men were investigated in the nine studies using a variety of instruments: the Beck Depression Inventory (BDI) [11,20,24], the Symptom Check List (SCL-90) [5,23], the Self-Rating Depression Scale (SDS) [19], the Psychological General Well-Being Index (PGWB) [6], the Patient Health Questionnaire-9 (PHQ-9) [21], and the Lubin's Depression Adjective Checklist Scale (DACL) [22]. The depression levels of women before proceeding with IVF treatment were presented in seven studies.…”
Section: Depressionmentioning
confidence: 99%
“…However, infertile women may feel pressure to appear more psychologically 'healthy' before undergoing IVF, in the fear that reporting symptoms of depression or anxiety might make them ineligible for treatment [9]. Lewis et al demonstrated that women in the IVF group reported depressive symptoms significantly less often than women in other groups [10]. As such, there is a need to investigate the depressive symptoms of women in infertile couples undergoing ART treatment in order to alleviate their suffering and enhance the therapeutic effect of IVF.…”
Section: Introductionmentioning
confidence: 97%
“…Depression and anxiety are the most common disorders among these (14). There are studies showing that both infertility and its treatment can cause these diseases (15). The rate of mild depression in females in infertility treatment varies from 12.0% to 54.0%.…”
Section: Introductionmentioning
confidence: 99%